Carfilzomib in multiple myeloma: unraveling cardiac toxicities - from mechanisms to diagnosis and management - Gao, Yi; Zhou, Di; Bai, Xue; Wang, Yunjie; Wang, Chenchen; Bi, Lintao (Frontiers in Pharmacology, 2025)
The survival rates of patients with hematological malignancies such as multiple myeloma have improved with advances in cancer treatment. However, the risk of cardiovascular disease associated with novel therapeutic agents, including proteasome inhibitors (PIs), is becoming increasingly evident. PIs act on proteasome peptidases, leading to cell cycle arrest or apoptosis. Carfilzomib (CFZ), an intravenously administered irreversible PI, exhibits pronounced cardiovascular toxicity that is characterized by heart failure, hypertension, arrhythmia, and ischemic heart disease (IHD). This review focuses on CFZ, details its applications in treating multiple myeloma, presents its potential mechanisms of cardiotoxicity and the incidence of cardiotoxic events, and provides recommendations for the evaluation and management of adverse cardiac events during the early treatment of patients with this drug.